Efektifitas Suhu Ekstraksi Terhadap Total Fenol Ekstrak Daun Kelor (Moringa Oleifera Lam) - Lisa Yusmita; Dewi Arziyah; M. Refoda Abdila AR (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2023)
This study aims to determine the effectiveness of Moringa leaf extract temperature on the yield of Moringa leaf extract. This research was carried out at the Laboratory for Analysis of the Properties of Materials and Agro-industrial Products Dharma Andalas University, Padang. The design used in this study was a completely randomized design with several extraction temperatures, namely 45 oC, 50 oC, 55 oC, 60 oC and 65 oC with 3 replications. The results of the observations were analyzed using ANOVA and if they were significantly different then they would continue using the DNMRT follow-up test at the 5% level. The results showed that the extraction temperature had a significant effect on the total phenol of Moringa leaf extract.